Komunikasi Pemasaran Dinas Pariwisata Kabupaten Buleleng Dalam Meningkatkan Jumlah Wisatawan Di Buleleng - Putri, Niluh Wiwik Eka (Jurnal Komunikasi Profesional, 2019)
By using a qualitative descriptive approach, this is to explore the activities of the marketing department of the Buleleng Regency Tourism Office in implementing marketing communications to increase the number of tourists. The tourism sector is one of the factors that influence the economy of Buleleng Regency. Through a good marketing communication strategy in marketing, the results will be good too, this will also increase tourist visits and help economic growth in Buleleng Regency. Similarly, tourism marketing aims to inform, persuade, introduce and increase tourist consumers so that prospective tourists have a desire to visit Buleleng Regency. The strategy carried out by the Buleleng Regency Tourism Office in increasing the number of tourist visits included advertising through television electronic media, online media, brochures, banners. Then face-to-face sales (Personal Selling) by introducing tourism products that are the object of tourist attractions. Furthermore sales promotion (Sales Promotion) through writing or direct communication, and publicity (Publicity) in the form of commercial news about products that are broadcast both through print media and electronic media. As well as direct marketing (Direct Marketing) is a form of promotion carried out by persuading prospective tourists. This can be done through writing that tells the experience on a personal blog. So that prospective tourists who want to go to Buleleng Regency can read someone's experience on various internet sites related to tourism objects, entrance ticket prices, locations, and so on. In addition, based on (Marketing Max) there are 13 elements including Products, Prices, places, promotions, people, physical condition, process, brand, segmentation, service, positioning, sales, and targets.Keywords: Marketing Communication, Buleleng Tourism Service, TravelersÂ